THU0628 IMMUNE-RELATED ADVERSE EVENTS INDUCED BY CANCER IMMUNOTHERAPIES. BIG DATA ANALYSIS OF 13, 051 CASES (IMMUNOCANCER INTERNATIONAL REGISTRY). (June 2019) - Ramos-Casals, Manuel; Lambotte, Oliver; Kostine, Marie; Calabrese, Leonard; Suarez-Almazor, Maria; Bingham, Clifton; Radstake, Timothy R.; Baldini, Chiara; Schaeverbeke, Thierry; Gottenberg, Jacques-Eric; Schulze-Koops, Hendrik; Leipe, Jan; et al.
Abstract : Background: The ImmunoCancer International Registry (ICIR) is a Big Data-Sharing multidisciplinary network composed by 39 specialists in Rheumatology, Internal Medicine, Immunology and Oncology from 18 countries focused on immune-related adverse events (irAEs) related to cancer immunotherapies (CIs). Objectives: To analyse the worldwide scenario of irAEs associated with the use of CIs in this Century. Methods: The first objective of the ICIR has been the development of a systematic literature review crossing CIs terms with immune diseases defined according to MedDRAVR 15.0. Results: The cumulated number of cases per year of irAEs has increased exponentially, with 12, 648 patients who developed 13, 051 irAEs reported until Dec 31, 2018: Combined CIs were used in 1962 (16%) patients, checkpoint inhibitors in 7099 (66%, overwhelmingly CTLA4 and PD1 inhibitors) and Tyrosine Kinase inhibitors in 3327 (31%); ipilimumab, nivolumab and pembrolizumab were associated with nearly 60% of reported cases. Organ-specific classification of irAEs is summarized in the figure: The Top10 irAEs included enterocolitis (18%), pneumonitis (12%), thyroiditis (11%), myocarditis (6%), myositis (5%), hypophysitis (5%), hepatitis (5%), neuropathy (4%), adrenal (3%) and joint involvement (3%). Most irAEs are organ-specific symptoms not fulfilled criteria of systemic/rheumatic diseases. Conclusion: More than 13, 000 cases of irAEs triggered by CIs have been reported, with the organ-specific autoimmune damage of the endocrine, digestive and pulmonary systems accounting for 70% of the total reported irAEs. Disclosure of Interests: Manuel Ramos-Casals: None declared, Oliver Lambotte: None declared, Marie Kostine: None declared, Leonard Calabrese Consultant for: Bristol-Myers-Squibb, Genentech and Astra-Zeneca., Maria Suarez-Almazor : None declared, Clifton Bingham Grant/research support from: BMS, Consultant for: AbbVie, BMS, Eli Lilly, Genentech/Roche, Janssen, Pfizer, Sanofi/Regeneron, Timothy R. Radstake: None declared, Chiara Baldini: None declared, Thierry Schaeverbeke: None declared, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Hendrik Schulze-Koops Grant/research support from: Novartis, Pfizer, Roche, Consultant for: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Paid instructor for: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Speakers bureau: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Jan Leipe Grant/research support from: Novartis, Pfizer; Scientific Support: Novartis, Pfizer, Consultant for: AbbVie, AstraZeneca, Bristol-Myers Squibb, Celgene, Hospira, Janssen-Cilag, LEO Pharma, Lilly, Novartis, Roche, Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Janssen-Cilag, Lilly, Novartis, MSD, Pfizer, Roche, Sanofi, UCB, cassandra calabrese Speakers bureau: Regeneron/Sanofi, Pilar Brito-Zerón: None declared, Alejandra Flores-Chávez: None declared, Belchin Kostov: None declared, Soledad Retamozo: None declared, Gustavo Citera: None declared, Eva Aguilar: None declared, Michael Richter: None declared, Merav Lidar: None declared, Benjamin Fisher Consultant for: Novartis, Roche, MedImmune, Bristol-Myers Squibb, Jean-Marie Michot: None declared, David Liew: None declared, Russell Buchanan: None declared, Marte Schrumpf-Heiberg: None declared, Philippe Guilpain: None declared, Debashish Danda: None declared, Peter Olsson: None declared, Yasunori Suzuki: None declared, Saadettin Kılıçkap: None declared, Gabriela Hernandez-Molina: None declared, Virginia Fernandes Moça Trevisani: None declared, Sonja Praprotnik: None declared, Ildiko Fanny Horváth: None declared, Naoto Azuma: None declared, Berkan Armagan: None declared, Munther Khamashta: None declared, Xavier Mariette Grant/research support from: Servier, Consultant for: AstraZeneca, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Pfizer, UCB Pharma